Using â€œSustainable Developmentâ€ Computer Program to Determine the Environmental Safety of the Regions - O. Soloshych, I.; I. Pochtovyuk, S. (International Journal of Engineering and Technology, 2018)
The article is devoted to the problem of determining the environmental safety of the country or its regions. It has been shown that existing software provides for automatic identification of only individual indicators or constituents of environmental safety. To eliminate these shortcomings, a methodology for assessing the environmental safety of the country or its regions has been substantiated and a model for building "Sustainable Development" software program has been developed. The paper gives the examples of the application of the developed "Sustainable Development" software program, which uses a system of basic indicators, combined in homogeneous groups â€“ economic, social, and environmental. The use of the software for any country in the world is substantiated, provided that the relevant empirical data are entered in order to develop the strategic purposes of the development of the regions and the entire country.Â Â